Novel therapeutic and drug development strategies for tobacco use disorder: endocannabinoid modulation. (1st September 2020) - Butler, Kevin; Le Foll, Bernard
ABSTRACT: Introduction: Tobacco use disorder (TUD) is a chronic relapsing condition. Existing pharmacotherapy can assist smokers to initiate smoking cessation, but relapse rates remain high. Novel therapeutics are required to help people quit and also to prevent relapse. The endocannabinoid system has been increasingly implicated in reward and addiction processes and the cannabinoid CB1 receptor inverse agonist rimonabant has been shown to be effective at promoting smoking cessation but has been associated with adverse psychiatric side effects. Areas covered: Multiple converging factors likely contribute to the maintenance of smoking and cause relapse including nicotine reinforcement, propensity to reinstate drug seeking (induced by nicotine priming, nicotine-associated cues, and stress), the severity of withdrawal signs and executive function status. Studies assessing the impact of endocannabinoid (CB1 receptor, CB2 receptor, anandamide, and 2-arachidonoylglycerol) modulation on these addiction-related factors are reviewed. Future research avenues are also discussed. Expert opinion: Endocannabinoid research in TUD is at a relatively early stage. Based on current evidence, CB1 receptor neutral antagonists and fatty acid amide hydrolase inhibitors demonstrate positive effects in studies assessing several addiction-related factors. This suggests they offer the greatest promise as novel cessation and anti-relapse agents.